Identifying dynamic games with serially-correlated unobservables - Yingyao Hu; Matthew Shum (The Johns Hopkins University, Department of Economics, 2008)
In this paper we consider the nonparametric identification of Markov dynamic games models in which each firm has its own unobserved state variable, which is persistent over time. This class of models includes most models in the Ericson and Pakes (1995) and Pakes and McGuire (1994) framework. We provide conditions under which the joint Markov equilibrium process of the firms' observed and unobserved variables can be nonparametrically identified from data. For stationary continuous action games, we show that only three observations of the observed component are required to identify the equilibrium Markov process of the dynamic game. When agents' choice variables are discrete, but the unobserved state variables are continuous, four observations are required.
Keywords: 330